Identification and characterization of a novel chitinase-like gene cluster (AgCht5) possibly derived from tandem duplications in the African malaria mosquito, Anopheles gambiae - Zhang, Jianzhen; Zhang, Xin; Arakane, Yasuyuki; Muthukrishnan, Subbaratnam; Kramer, Karl J.; Ma, Enbo; Zhu, Kun Yan (My University, 2011)
Insect chitinase 5 (Cht5), a well-characterized enzyme found in the molting fluid and/or integument, is classified as a group I chitinase and is usually encoded by a single gene. In this study, a Cht5 gene cluster consisting of five different chitinase-like genes (AgCht5-1, AgCht5-2, AgCht5-3, AgCht5-4 and AgCht5-5) was identified by a bioinformatics search of the genome of Anopheles gambiae. The gene models were confirmed by cloning and sequencing of the corresponding cDNAs and gene expression profiles during insect development were determined. All of these genes are found in a single cluster on chromosome 2R. Their open reading frames (ORF) range from 1227 to 1713 bp capable of encoding putative proteins ranging in size from 409 to 571 amino acids. The identities of their cDNA sequences range from 52 to 66%, and the identities of their deduced amino acid sequences range from 38 to 53%. There are four introns for AgCht5-1, two for AgCht5-2 and AgCht5-3, only one for AgCht5-4, but none for AgCht5-5 in the genome. All five chitinase-like proteins possess a catalytic domain with all of the conserved sequence motifs, but only AgCht5-1 has a chitin-binding domain. Phylogenetic analysis of these deduced proteins along with those from other insect species suggests that AgCht5-1 is orthologous to the Cht5 proteins identified in other insect species. The differences in expression patterns of these genes at different developmental stages further support that these genes may have distinct functions. Additional searching of the genomes of two other mosquito species led to the discovery of four Cht5-like genes in Aedes aegypti and three in Culex quinquefasciatus. Thus, the presence of a Cht5 gene cluster appears to be unique to mosquito species and these genes may have resulted from gene tandem duplications.
Keywords: African malaria mosquito; Anopheles gambiae; Chitinase; Gene cluster; Gene duplication; Glycoside hydrolase